Characteristics of Bronchial Asthma Sufferers at The Pulmonary Polyclinic Dr. H. Chasan Boesoirie Ternate Hospital - Ghafur, Rizky A.; Prihanto, Eko Sudarmo Dahad; Anwar, Mawardy (Jurnal Medis Islam Internasional, 2025)
Introduction: Bronchial asthma is a reversible obstructive airway disease characterized by lung inflammation and airway hypersensitivity. In 2018, the incidence of bronchial asthma in North Maluku Province reached 4,723 cases. Patient characteristics are thought to contribute to the occurrence of bronchial asthma. Objective: This study aimed to identify the characteristics of bronchial asthma sufferers at the Pulmonary Polyclinic of Dr. H. Chasan Boesoirie Hospital in Ternate. Methods: This research used a retrospective descriptive design with a cross-sectional approach. The variables studied included asthma severity, gender, age, occupation, and education level. Secondary data were collected from medical records at Dr. H. Chasan Boesoirie Hospital between 2019 and 2022. Results: Among the 40 samples, most patients had moderate persistent asthma (47.5%). The majority were female (70%), aged 26–45 years (42.5%), self-employed (55%), and had completed high school education (70%). Conclusions: The study concludes that bronchial asthma at Dr. H. Chasan Boesoirie Hospital in Ternate is more prevalent among females, individuals aged 26–45 years, those who are self-employed, and those with a high school education level. Moderate persistent asthma was the most common severity observed. These results highlight the importance of considering demographic and occupational characteristics in the management and prevention of bronchial asthma.